Rituximab in treatment of post-transplant lymphoproliferative disease after allogeneic stem cell transplantation - Gil, Lidia; Styczyński, Jan (Contemporary Oncology/Współczesna Onkologia, 2011)
Post-transplant lymphoproliferative disease (PTLD) after haematopoietic stem cell transplantation is a life-threatening complication and the number of patients at risk is increasing over time. In the majority of patients Epstein-Barr virus-related PTLD (EBV-PTLD) is diagnosed with a histological picture of B-cell lymphoma. In 2009 recommendations for diagnosis, monitoring and treatment of patients with EBV-PTLD were published. Definitions of preemptive treatment and therapy of probable or proven PTLD were introduced. Results of preemptive treatment and therapy of documented PTLD are discussed in this paper, with the emphasis on monoclonal antibody anti-CD20 rituximab effectiveness and indications for its applications. A comprehensive review of reported cases of PTLD and summary of results indicate that rituximab in monotherapy or in combination treatment is successful in 63% of confirmed PTLD cases and in 89% when used preemptively. Still, an analysis of factors determining the response to therapy is lacking.